Experiences with immunization against Theileria parva using p67, a sporozoite surface antigen - Musoke, A.J.; McKeever, Declan J.; Morzaria, S.P.; Nkonge, C.; Nene, Vishvanath M. (International Laboratory for Research on Animal Diseases, 1995)
Theileria parva, a protozoan parasite of cattle, causes a disease called East Coast fever. The disease is of economic importance because it causes high morbidity and mortality and limits the development of the cattle industry. This paper highlights the experiences with immunization against Theileria parava using p67, a sporozoite surface antigen. Topics discussed include mechanisms of protection against East Coast Fever, cloning and expression of p67, immunization and challenge of cattle, and B-cell epitope mapping.